Aksi dan Motif Seseorang Melakukan Kecurangan dalam Pengelolaan Dana Kemahasiswaan - Adrian Izaak Rompis; Aprina Nugrahesthy Sulistya Hapsari (Postgraduate Program Merdeka University, 2022)
This study aims to explore the motivating motive of students who are members of the Student Association (in university X commonly referred to HMP) committee in committing fraud in the management of student funds using the fraud hexagon approach (pressure, rationalization, opportunity, capability, arrogance, collusion) and herding. This research was conducted using a qualitative descriptive method on 25 HMP at university X with primary data obtained through the distribution of open questionnaires to students involved in student fund management, semi-structured interviews, and observations, as well as secondary data in the form of documentation of related evidence. The results showed that all the motives in the fraud hexagon and the herding motive encouraged HMP functionaries to commit fraud in the management of student funds with various fraud modes. Other findings also show that fraudulent practices in the management of student funds have become a culture in the HMP organization